2013
DOI: 10.1016/j.ultsonch.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between iodide dosimetry and terephthalic acid dosimetry to evaluate the reactive radical production due to the acoustic cavitation activity

Abstract: Acoustic cavitation plays an important role in sonochemical processes and the rate of sonochemical reaction is influenced by sonication parameters. There are several methods to evaluate cavitation activity such as chemical dosimetry. In this study, to comparison between iodide dosimetry and terephthalic acid dosimetry, efficacy of sonication parameters in reactive radical production has been considered by iodide and terephthalic acid dosimetries. For this purpose, efficacy of different exposure parameters on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…5b. This is different from the studies of Ebrahiminia et al and Barati et al, who showed that continuous ultrasound also induced higher cavitation activities than 20% DC with a compensated duration [27,31]. One explanation is that the sonication durations in our study were relatively short (1-10 min), whereas, in the studies of Ebrahiminia et al and Barati et al, the durations were in the range of 20-100 min.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…5b. This is different from the studies of Ebrahiminia et al and Barati et al, who showed that continuous ultrasound also induced higher cavitation activities than 20% DC with a compensated duration [27,31]. One explanation is that the sonication durations in our study were relatively short (1-10 min), whereas, in the studies of Ebrahiminia et al and Barati et al, the durations were in the range of 20-100 min.…”
Section: Discussioncontrasting
confidence: 99%
“…Ebrahiminia et al used iodide dosimetry to evaluate the inertial cavitation activity and showed that continuous ultrasound produced more sonochemical effects than burst ultrasound [31]. Our results also showed that with the same sonication duration, continuous ultrasound induced more PpIX decomposition than burst ultrasound (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Lida et al (2005) showed that the degree of gas saturation, the type of gas, and the temperature of a sonicated dosimeter solution at different sonication frequencies play an important role in determining the extent of inertial cavitation occurrence. Further, Ebrahiminia et al (2013) observed that sonication frequency plays an important role for reactive radical generation in the medium and showed that with increasing the sonication frequency, the cavitation yield increased when the frequency was greater than 250 kHz.…”
Section: Effect Of Sonication Frequencymentioning
confidence: 99%
“…They observed that the concentration of KI and temperature affect the cavitation yield of the system such that the iodine production is proportional to both conditions. Furthermore, Ebrahiminia et al (2013) studied the efficacy of different exposure parameters on cavitation production by 1 MHz ultrasound using iodide dosimetry and reported that with increasing time of sonication or intensity, the absorbance is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Microbubbles grow and collapse when irradiated with US (8,9), and during sonoporation, H 2 O 2 is produced in the medium (10). This free radical production can be measured using the starch-iodide method (11), by which free radicals are quantified when combined with potassium iodide (KI) (12).…”
Section: Introductionmentioning
confidence: 99%